Instrument for Measuring Patient Safety Culture: Literature Review - Yumna Nur Millati Hanifa; Inge Dhamanti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
The implementation of safe and quality care with attention to patient safety, requires organization’s effort to create and cultivating patient safety culture. The purpose of this article was to map the instruments used in measuring patient safety culture in healthcare organizations. The method used integrated literature review from various sources of research articles published from 2015 to 2020. The article included if it was available in full text and open access as well as articles described the instruments of patient safety culture or measurement of patient safety culture using one of the instruments of measurement of patient safety culture. The results of the literature review unravel the findings of three instruments such as HSOPSC (Hospital Survey on Patient Safety Culture), MaPSaF (Manchester Patient Safety Assessment Framework) and SAQ (Safety Attitudes Questionnaire). We concluded all three instruments contained four dimensions of patient safety culture, namely open culture, just culture, reporting culture and learning culture and were widely used to measure patient safety culture in hospitals, primary health facilities and other health facilities.